PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2019)
This research was conducted on cigarette companies listed on the Indonesia Stock Exchange (BEI) in the 2010-2017 period. However, due to limited distance, time, and easier availability of information, data collection was based on secondary data, namely research on data collected after the fact. Research is carried out on an object within a certain period where the data taken is the financial reports of cigarette companies listed on the Indonesia Stock Exchange (BEI). Based on the research result, it shows that Return on Assets, Earning Per Share, Price Earning Per Ratio and Return on Equity together have an effect on stock prices.